Role of Bureacracy in Promoting Productivity in Local Governments: A Case Study of Aminit Sub County in Bukedea District - Stephen Malinga (Uganda Christian University, 2024)
The study aimed to investigate the role of bureaucracy in promoting productivity in local government, focusing on Aminit Sub-County Subcounty in Bukedea District. Specifically, it sought to examine how bureaucratic structures, initiatives, and challenges affect employee productivity and public services. Utilizing a cross-sectional survey approach, the research collected data from 36 respondents out of a population of 40. This method was chosen for its efficiency and cost-effectiveness in gathering data. The findings of the study revealed significant insights into the relationship between bureaucratic structures and employee productivity. Additionally, it shed light on the impact of bureaucratic initiatives on public services and the challenges faced in this context. The study concluded that effective bureaucratic structures and initiatives are crucial for promoting productivity in local government. Addressing bureaucratic challenges is essential for enhancing employee productivity and delivering efficient public services. These findings underscore the importance of strategic management of bureaucracy in local government settings.